IMPLEMENTASI METODE EVERYONE IS A TEACHER HERE DALAM MENINGKATKAN KEMAMPUAN PUBLIC SPEAKING SISWA PADA PELAJARAN SKI KELAS X SMA NU GENTENG BANYUWANGI - Anis Fauzi; Imam Wahyudi (Tarbiyatuna Kajian Pendidikan Islam, 2023)
The learning method is one of the important components needed in learning because it becomes a means of interaction between educators and students. Because learning methods are not always in accordance with the conditions of students and learning materials, it is necessary for the competence of an educator to determine appropriate and appropriate learning methods. This study aims to describe the implementation of the everyone is a teacher here method in improving students' public speaking skills in class X SKI at SMA NU Genteng Banyuwangi. This study uses a qualitative approach to the type of descriptive qualitative research. Data collection by interview, observation and documentation methods. The researcher as the main instrument, the subject of this research is SKI teacher, and several students of class X science. The sampling technique used was purposive sampling. The validity of the data is done by triangulation of sources. Data analysis uses data reduction, data presentation, and drawing conclusions. Based on the results of interview data and observations that have been made by researchers that the implementation of the everyone is a teacher here method includes planning, namely lesson plans, syllabus. The implementation is the teacher delivers the material, distributes paper, makes questions, the paper is collected randomly, students submit questions and answers, other students give responses, take turns until they are finished. Evaluation is closing and assessment. The supporting factors are adequate school facilities, students play an active role, train thinking power, questions attract students' attention, ability to think, self-confidence. While the inhibiting factors are that it takes a long time, students feel afraid and lack confidence, it is difficult to make questions that are according to students' abilities, requiring exposure of the material first.